Association of Palatal Rugae Patterns In The Maternal Lineage Between Biological Mothers And Daughters of The Minangkabau Ethnic Group In Padang City - Andi Aisyah Farra Arman; Nila Kasuma; Reno Wiska Wulandari; Dewa Made Wedagama (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Palatal rugae are unique, anatomically stable ridges in the oral cavity that serve as reliable markers for forensic identification and genetic research. The Minangkabau ethnic group, known for its matrilineal kinship system, to provides a unique context to for exploring the hereditary transmission of such traits. This study aimed to examine the morphological similarities and differences in palatal rugae patterns between biological mothers and their daughters within the Minangkabau ethnic group in Padang City, Indonesia. Material and Methods: An analytical cross-sectional design was employed involving 53 mother-daughter pairs of confirmed Minangkabau descent. Intraoral digital scans were used to record rugae patterns which were categorized by shape and size based on established classifications. Statistical analysis was conducted using the Mann-Whitney U test to assess intergenerational associations. Results and Discussion: Primary and secondary rugae patterns showed strong morphological similarities between mothers and daughters, indicating heritability. Notably, the wave-shaped rugae pattern was significantly more prevalent in daughters (p < 0.05). Conclusion: Palatal rugae patterns, particularly primary and secondary types, demonstrate maternal inheritance and have potential forensic relevance. The presence of unique ethnic-specific traits underscores the need for broader population-based classifications in forensic odontology and antropology